2021
DOI: 10.1002/hrdq.21435
|View full text |Cite
|
Sign up to set email alerts
|

Navigating tensions in rendering both career and psychosocial functions: An exploratory study of hybrid multiplex developmental relationships

Abstract: This study presents a different perspective on multiplex developmental relationships encompassing both career and psychosocial functions by highlighting the unique contradictions and coping mechanisms underlying these relationships. The in‐depth qualitative comparative case study analyses of 73 developmental relationships of 20 nascent technology entrepreneurs yielded four tensions: disclosure‐privacy, dependence‐independence, criticism‐confirmation and formality‐informality. Entrepreneurs and their developers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In the literature on students' socialisation, developmental relationships primarily encompass student-faculty and student-peer relationships and interactions (Pascarella & Terenzini, 2005). These developmental relationships are pivotal for effective socialisation, as they are considered to fulfil two fundamental support functions: career and psychosocial support (Ghosh & Nadkarni, 2022;Murphy et al, 2017). Research shows that frequent interactions with faculty who are insiders lead to faster adjustment to the academic environment as they form informal learning networks (Noy & Ray, 2012).…”
Section: Socialising Into the 'Ideal Academic': Interactional And Con...mentioning
confidence: 99%
“…In the literature on students' socialisation, developmental relationships primarily encompass student-faculty and student-peer relationships and interactions (Pascarella & Terenzini, 2005). These developmental relationships are pivotal for effective socialisation, as they are considered to fulfil two fundamental support functions: career and psychosocial support (Ghosh & Nadkarni, 2022;Murphy et al, 2017). Research shows that frequent interactions with faculty who are insiders lead to faster adjustment to the academic environment as they form informal learning networks (Noy & Ray, 2012).…”
Section: Socialising Into the 'Ideal Academic': Interactional And Con...mentioning
confidence: 99%
“…Contrary to the inequality‐reducing claim, Nielsen and Nørreklit (2009) argued that MAC is based on power inequality, with Welman and Bachkirova (2010) insisting that neither party is comfortable with the process. Indeed, Ghosh and Nadkarni (2021) noted that tension is inherent in any developmental process; nonetheless, Nielsen and Nørreklit (2009) contended that executive coaching involves control of the employees' spirit and may serve the self‐interest of the manager rather than the interest of the coachee. In a meta‐analysis of coaching articles conducted by Sonesh et al (2015) to locate power relations, it was found that coaching has the strongest impact on the coachee (for example, more than setting goals).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In multiple case studies, researchers must establish a commonality across the cases that allows them to analyze and identify qualities that are replicable or transferable to related circumstances or contexts. For example, Ghosh and Nadkarni’s (2022) multiple-case study incorporated interviews, archival data, and observations to respond to two research questions: “What tensions arise in hybrid multiplex developmental relationships? How do developers and developees address them?” (p. 71).…”
Section: Approaches To Qualitative Researchmentioning
confidence: 99%